Maintenance of Meat Grinding Machines at CV. Solo Indah in Palu City - Musfara Kaharuddin; Asngadi Asngadi; Sulaeman Miru; Kadek Agus Dwiwijaya (Penerbit Goodwood, 2025)
Purpose: This study analyzes the maintenance practices of meat grinding machines at CV Solo Indah in Palu City, focusing on preventive and corrective strategies, and provides recommendations to improve efficiency and reduce breakdowns. Methodology/Approach: Conducted over three months using a descriptive quantitative approach, the study employed direct observation, structured interviews, and documentation. Machine components were evaluated using fishbone diagrams, cost analysis, and efficiency calculations with the formula TC = (F × RI) / (RO × P). Tools included maintenance records, interview guides, and Microsoft Excel. Results/Findings: All major components experienced at least one failure in 2024. The gearbox, machine frame, and feeder had the highest repair costs. The total maintenance cost was Rp13,674,500, with preventive maintenance accounting for 53.68% and corrective for 46.32%. This indicates a balanced and efficient maintenance system categorized as “very efficient” under industry benchmarks. Conclusions: CV Solo Indah implements both preventive and corrective maintenance effectively, though corrective costs remain relatively high. Prioritizing preventive actions for costly components like the gearbox can reduce overall expenses. Fishbone analysis identified root causes in manpower, machine, method, material, environment, and measurement aspects. Limitations: The study focuses on one company and a short 3-month period, limiting generalization to broader industry trends. Contribution: This research enriches industrial engineering and operations management literature, especially for SME-scale meat processing, by providing practical insights to enhance maintenance systems, lower costs, and increase productivity.